Ultra-restrictive red blood cell transfusion strategies in extensively burned patients - Yiran Wang; Zhikang Zhu; Deqing Duan; Wanting Xu; Zexin Chen; Tao Shen; Xingang Wang; Qinglian Xu; Hongyan Zhang; Chunmao Han (Scientific Reports, 2024)
Abstract In recent years, due to the shortage of blood products, some extensive burn patients were forced to adopt an “ultra-restrictive” transfusion strategy, in which the hemoglobin levels of RBC transfusion thresholds were < 7 g/dl or even < 6 g/dl. This study investigated the prognostic impacts of ultra-restrictive RBC transfusion in extensive burn patients. This retrospective multicenter cohort study recruited extensive burns (total body surface area ≥ 50%) from three hospitals in Eastern China between 1 January 2016 and 30 June 2022. Patients were divided into an ultra-restrictive transfusion group and a restrictive transfusion group depending on whether they received timely RBC transfusion at a hemoglobin level < 7 g/dl. 1:1 ratio propensity score matching (PSM) was performed to balance selection bias. Modified Poisson regression and linear regression were conducted for sensitive analysis. Subsequently, according to whether they received timely RBC transfusion at a hemoglobin level < 6 g/dl, patients in the ultra-restrictive transfusion group were divided into < 6 g/dl group and 6–7 g/dl group to further compare the prognostic outcomes. 271 eligible patients with extensive burns were included, of whom 107 patients were in the ultra-restrictive transfusion group and 164 patients were in the restrictive transfusion group. The ultra-restrictive transfusion group had a significantly lower RBC transfusion volume than the restrictive transfusion group (11.5 [5.5, 21.5] vs 17.3 [9.0, 32.5] units, p = 0.004). There were no significant differences between the two groups in terms of in-hospital mortality, risk of infection, hospital length of stay, and wound healing time after PSM or multivariate adjustment (p > 0.05). Among the ultra-restrictive transfusion group, patients with RBC transfusion threshold < 6 g/dl had a significantly higher hospital mortality than 6–7 g/dl (53.1% vs 21.3%, p = 0.001). For extensive burn patients, no significant adverse effects of ultra-restrictive RBC transfusion were found in this study. When the blood supply is tight, it is acceptable to adopt an RBC transfusion threshold of < 7 g/dL but not < 6 g/dL.